EDUKASI STUNTING (EDITING) SEBAGAI UPAYA PENINGKATAN PENGETAHUAN GIZI IBU DI WILAYAH BANTEN - Mukhlidah Hanun Siregar; Hanifa Utami; Akhmad Kholilulloh; Khalid Ibu Sunan; Mutia Tri Anggini; Yusniar Wulan Yuliyanti Putri (Universitas Majalengka, 2022)
Stunting or short in toddlers is one malnutrition that occurs for a long time and is caused by various factors. This condition can be prevented by paying attention to the fulfillment of balanced nutrition in the First 1000 Days of Life. Analysis of the situation showed that most mothers have heard of stunting but did not understand balanced nutrition patterns for stunting prevention. This activity was carried out to provide knowledge to mothers about stunting by comparing two methods (online and offline) in the Banten area. The results found that there was no difference in maternal knowledge scores in the two methods, so it can be concluded that both online and offline methods were able to provide knowledge to mothers about stunting. These two methods can be recommended for use in stunting education by paying attention to the advantages and disadvantages of each method. The online method needs to pay attention to the availability of the internet and the ownership of gadgets, while the offline method must maintain the implementation of education to be conducive so that the information conveyed can be received properly. In the future, online methods can be developed into several series so that mothers obtain information gradually so that they are easier to understand without taking up much time.